Investigation of the magnetic properties of nanometric SrSmCoNi ferrite/PST matrix. Issue 7 (August 2015) - Ali, Irshad; Islam, M.U.; Ashiq, Muhammad Naeem; Shakir, Imran; Karamat, Nazia; Ishaque, M.; Akhtar, Majid Niaz; Khan, Hasan M.; Irfan, Muhammad; Khan, Muhammad Azhar
Abstract: Y-type hexa-ferrite Sr1.8 Sm0.2 Co2 Ni1.50 Fe10.50 O22 was synthesized via micro-emulsion route. Ferrite/PST composites were obtained by mixing the different ferrite ratio in the pure PST matrix. The microstructure was examined by scanning electron microscopy (SEM) and exhibited heterogonous distribution of grains. A keen observation of these SEM images revealed that the grain morphology changes noticeably with increasing ferrite filler contents. The electrical modulus, Cole–Cole plots and quality factor of ferrite polymer composites have been investigated in the frequency range (1 MHz to 3 GHz). The field dependent magnetic properties of the prepared samples were investigated at room temperature by using vibrating sample magnetometer (VSM). The shape of hysteresis loops and linearity of M s, M r, H c values vs. ferrite contents unfold that the ferrite nanoparticles are evenly dispersed within the composite. The occurrence of resonance at high frequency suggests that the present investigated composite samples are best candidate for multilayer chip inductors.